2015
DOI: 10.1186/s12895-015-0024-z
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the global resource of eczema trials (GREAT database)

Abstract: BackgroundEczema (syn. Atopic Eczema or Atopic Dermatitis) is a chronic, relapsing, itchy skin condition which probably results from a combination of genetic and environmental factors. The Global Resource of EczemA Trials (GREAT) is a collection of records of randomised controlled trials (RCTs) for eczema treatment produced from a highly sensitive search of six reference databases. We sought to assess the sensitivity of the GREAT database as a tool to save future researchers repeating extensive bibliographic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…We followed a predefined protocol and the PRISMA statement. Our search was performed using a validated search filter . Two reviewers independently extracted data for each study, and disagreements or uncertainties were resolved through discussions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We followed a predefined protocol and the PRISMA statement. Our search was performed using a validated search filter . Two reviewers independently extracted data for each study, and disagreements or uncertainties were resolved through discussions.…”
Section: Discussionmentioning
confidence: 99%
“…The Global Resource for Eczema Trials (GREAT) database was used to identify all RCTs on AE treatments published since 2000, as a previous review already evaluated many RCTs before 2000 . The GREAT database (http://www.greatdatabase.org.uk) contains records of all RCTs of treatments for established AE published since the inception of Medline (1966) and Embase (1980), the Cochrane Library and the Skin Group Specialised Register databases, plus the CINAHL, Allied and Complementary Medicine Database and LILACS databases from 2000 onwards . RCTs published between January 2000 and April 2014 were included.…”
Section: Methodsmentioning
confidence: 99%
“…A strength of this study was the use of the GREAT database, which searches 6 databases, including 3 specialist databases. A recent study showed a high sensitivity of the GREAT database, with 94% of trials cited in systematic reviews on eczema treatments listed in the GREAT database (104). The GREAT database therefore is considered a primary and comprehensive source to identify eczema RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…One group included articles that conduct systematic reviews using a variety of online databases. These covered a wide variety of therapies, including medications, brachytherapy, exercise, nutrition, and ophthalmological treatments [101][102][103][104][105][106][107][108]. Another group analyzed various trends in publications, such as how researchers access the literature, extent to which studies comply with registration and reporting requirements, reasons for study termination, transparency regarding sponsorship and conflicts of interest, and inclusion of patient-reported outcomes [109,110,[111][112][113][114][115].…”
Section: Analyzing Study Publicationsmentioning
confidence: 99%